(untitled) (Annals of Medical Research, 2024)
Aim: This study examines the effects of pneumothorax and pneumomediastinum on the mortality and morbidity of patients with respiratory virus infections. It analyses blood parameters and the Systemic Immune Inflammation Index (SII) in patients who acquired these complications compared to those who did not. Materials and Methods: We conducted a retrospective assessment of 2246 COVID-19 patients who received treatment at our medical facility between August 2020 and February 2021. This study included a total of 118 patients who were admitted to the hospital due to a respiratory virus illness. The patients were categorised into two groups: one consisting of individuals who experienced pneumothorax and/or pneumomediastinum, and the other consisting of individuals who did not acquire these complications. Both groups had an equal number of participants. The study analysed many factors including metabolic profiles, hemogram results, length of hospital stay, SII levels, and the incidence of pneumothorax, with a focus on their association with morbidity and mortality outcomes. Results: Significantly, female patients who experienced pneumothorax during COVID-19 treatment exhibited a worse mortality rate. Patients with pneumothorax had elevated leukocyte and neutrophil counts, along with heightened systemic immune-inflammation index (SII) and decreased levels of total protein and albumin. The data highlight the potential importance of specific blood measurements, as well as the presence of pneumothorax, as indications for death in patients with respiratory virus infections. Conclusion: For enhanced patient outcomes, it is important to closely monitor and manage female patients who get pneumothorax after receiving therapy for respiratory virus infection.